Implementation of Structuralism Approach in Nahwu Learning with Bandongan Method in Indonesia - Muhammad Rizal Falaqi (Journal of Advanced Research in Social Sciences and Humanities, 2023)
Aim: This research aims to describe the application of structuralism in learning Nahwu using the Bandongan method at Nurul Huda Mergosono Junior High School Indonesia.Methodology: This research uses a post-positivist model with a quasi-qualitative approach. The primary data source in this research is the observations of students at Nurul Huda Mergosono Junior High School Indonesia. While the secondary data source is from journals and books related to this research. The data collection techniques used are observation, interviews, and documentation. Meanwhile, the data analysis techniques are data reduction, data collection, and data presentation.Findings: The conclusion of this research is to discover 5 steps in the application of structuralism in learning Nahwu using the Bandongan method at Nurul Huda Mergosono Junior High School, which are: 1) Selecting classical texts of Bandongan method with a structural focus, 2) Linking each rule to the linguistic structure, 3) Using structural tables and charts, 4) Structural deductive approach, and 5) Cooperative learning using Bandongan method.Implications/Novel Contribution: The study bridges the research gap by application of structuralism approach in a school climate and came up with five steps of effective implementation for the use of policy makers, school leaders and educational scholars.